2017
DOI: 10.1186/s12981-017-0131-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of antiretroviral treatment monitoring in the era of decentralized HIV care: a systematic review

Abstract: BackgroundRegular monitoring of HIV patients who are receiving antiretroviral therapy (ART) is required to ensure patient benefits and the long-term effectiveness and sustainability of ART programs. Prompted by WHO recommendations for expansion and decentralization of HIV treatment and care in low and middle income countries, we conducted a systematic review to assess the feasibility of treatment monitoring in these settings.MethodsA comprehensive search strategy was developed using a combination of MeSH and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 46 publications
2
50
0
4
Order By: Relevance
“…While almost all sites reported universal HIV treatment as the standard of care, we found considerable variation in site‐level practices related to rapid ART initiation, with private sector sites and sites in high‐resource settings more likely to report longer times to treatment initiation. Consistent with other research , we also found considerable variation in capacity for viral load monitoring, and almost one‐third of the sites implementing Treat All indicated that they could not routinely request or perform viral load testing. Such gaps were particularly prevalent among sites located in rural areas and in low‐income countries, as well as in countries where Treat All was adopted more recently.…”
Section: Discussionsupporting
confidence: 89%
“…While almost all sites reported universal HIV treatment as the standard of care, we found considerable variation in site‐level practices related to rapid ART initiation, with private sector sites and sites in high‐resource settings more likely to report longer times to treatment initiation. Consistent with other research , we also found considerable variation in capacity for viral load monitoring, and almost one‐third of the sites implementing Treat All indicated that they could not routinely request or perform viral load testing. Such gaps were particularly prevalent among sites located in rural areas and in low‐income countries, as well as in countries where Treat All was adopted more recently.…”
Section: Discussionsupporting
confidence: 89%
“…Monitoring systems with performance indicators should be implemented, ideally with integrated, automated systems that identify patients in need of VL-testing [67]. Creating demand for VL among clinicians and patients will be critical [20,21,35,56,[68][69][70][71]. A recent modelling study predicted that switching patients on efavirenz-based first-line after only one high VL will significantly decrease mortality related to delayed switch [72], POC-VL and same day results would further support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing their VL status can motivate patients to adhere to treatment [9,10], and can allocate virally suppressed patients into differentiated models of care [11,12]. Yet despite being associated with better treatment outcomes and the prevention of acquired drug resistance [6,13], routine VL-monitoring remains under-utilized in resource-limited settings [14][15][16][17][18][19][20][21]. It was estimated that less than 50% of people on ART in resource-limited settings received an annual VL test in 2017 [22].The test's cost and complexity remain barriers to its use, as does a lack of understanding by some clinicians about VL's long-term patient benefits and its role in prolonging the longevity of treatment regimens [18,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal microbiota of HIV patients appears to contain higher levels of pathogens, such as Pseudomonas aeruginosa and Candida albicans and reduced levels of LAB species. Thus, gut reconditioning through probiotic administration could be protective for the gut surface and delay the progression to AIDS [93,94] (Figure 3). In young HIV infected subjects, elevated inflammation levels, persistent immune activation and dysfunction will be observed for many years.…”
Section: Probiotics As a New Therapeutic Approach That Might Improve mentioning
confidence: 99%